Automatic Text Alignment Using Recursive Hapax-Based Cut-Through Fragmentation - Ng , Pek Kuan (2012)
Communication over the Internet becomes the necessity of life. Multi-lingual machine translation systems are developed to support such communication. One of the most commonly used approaches is the example-based approach which requires a large set of examples as reference. These examples are prepared by aligning the parallel texts either manually or semi-automatically with human intervention. This requires much effort and is time-consuming considering the large number of examples needed to ensure the quality of the translation. Moreover, the fact that humans make mistakes and has preferences raises the consistency issue. Hence, there is an urgent need to develop an automatic aligner.